Analisis konsekuensi hukum pelanggaran keterlambatan pemberitahuan pengambilalihan saham: Studi kasus putusan KPPU Nomor 13/KPPU-M/2022 - Yanti, Ari (Maliki Interdisciplinary Journal, 2024)
The purpose of this research is to examine the legal consequences that arise as a result of the KPPU Decision Number 13/KPPU-M/2022 concerning the impact of delayed notification regarding the acquisition of shares of PT Bakti Gemilang Anak Sejahtera by PT Rumah Kasih Indonesia. The background of this study emerges from the fact that the KPPU decision indicates a violation of regulations governing the notification of share acquisitions. The research methodology employed involves a normative juridical approach, focusing on the analysis of written law and a case-based approach through the evaluation of KPPU decisions. A conceptual approach is also applied in this study, as well as a perspective from Islamic law. The data used is obtained from the examination of KPPU decisions and references to legal regulations related to share acquisition reporting in Indonesia. The findings of this research reveal that in the KPPU Decision Number 13/KPPU-M/2022, it is affirmed that PT Rumah Kasih Indonesia has violated legal provisions regarding the delay in providing notification concerning the acquisition of shares of PT Bakti Gemilang Anak Sejahtera. The legal consequences of this violation can manifest as administrative sanctions, fines, or corrective actions determined by the KPPU. This study holds significant implications in understanding the legal repercussions of violations in share acquisition notifications. The results of this study are expected to provide deeper insights into the importance of companies adhering to regulations, along with the potential consequences that may arise if these rules are breached.